Risk stratification in patients with Brugada syndrome: the role of the late potentials evaluated by signal-averaged ECG. (14th October 2021) - Cunha, N.P.D; Rodrigues, T; Silverio Antonio, P; Couto Pereira, S; Brito, J; Alves Da Silva, P; Valente Silva, B; Neves, I; Nunes-Ferreira, A; Lima Da Silva, G; Carpinteiro, L; Cortez-Dias, N; et al.
Abstract: Introduction: Brugada syndrome (BS) is a relevant cause of sudden death in individuals without structural heart disease. The accuracy of the available methods for risk stratification is very limited and the investigation of new methodologies to improve the identification of patients at risk is under intensive investigation. Recently the pathophysiological relevance of anomalous, fragmented and prolonged electrograms on the epicardial surface of the right ventricular outflow tract (RVOT) has been described. Therefore, the study of signal-averaged ECG (SA-ECG) has become attractive since it may allow the non-invasive evaluation of these electrical anomalies. In order to maximize the detection capacity and to focus the evaluation in the RVOT, we developed an alternative methodology of electrode positioning directed to this area of interest. Purpose: To characterize the study of late potentials (LP) by SA-ECG in patients with SB and to evaluate its association with the occurrence of arrhythmia events. Methods: Prospective single centre study of patients (pts) with BS. LP were evaluated by SA-ECG with determination of the total filtered QRS duration (fQRS), root mean square voltage of the 40 ms terminal portion of the QRS (RMS40) and duration of the low amplitude electric potential component (40 microV) of the terminal portion of the QRS (LAS40) in conventional and modified leads (addressed to RVOT). The association of LP with the risk of definite malignant dysrhythmias due to sudden death, ventricular fibrillation, ventricular tachycardia or appropriate shock of the implantable cardioverter defibrillator (ICD) was evaluated and the acuity of the prognostic stratification was determined by the area under the receiver operator characteristic curve (ROC). Results: A total of 76 pts (69.7% men, age 48±12 years) were studied, of which 33 had a spontaneous type 1 pattern and 43 had a type 1 pattern induced by flecainide. During a median follow-up of 1.6 years, 13 pts (17.1%) had symptoms potentially related to BS and 6 (10.5%) had malignant arrhythmias [including two pts who suffered sudden death (2.6%). The pts who had malignant dysrhythmias presented higher values of fQRS (125±23 vs. 108±18, p=0.046) and LAS40 (54±13 vs. 40±11, p=0.014), and lower values of RMS40 only in the modified leads (11±5 vs. 22±19, p=0.041). The parameters of the SA-ECG were significant prognostic predictors. The acuity of each of the parameteres alone was moderate and the parameters that were identified as more powerful predictors of risk were those derived from the modified leads (Figure). Conclusion: The LP evaluated by SA-ECG may be relevant in the prognostic stratification of patients with BS, since it seems to be associated with the risk of malignant ventricular arrhythmias. Funding Acknowledgement: Type of funding sources: None.